CORPORATE SOCIAL RESPONSIBILITY (CSR) DISCLOSURES AND INVESTOR CONFIDENCE: A MULTI-COUNTRY ANALYSIS - Lisbet Situmorang; Adrian Handa (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2026)
This study aims to analyze the role of Corporate Social Responsibility (CSR) disclosure in shaping and strengthening investor trust across countries. Increasing investor attention to non-financial aspects encourages companies to disclose CSR information as part of their corporate transparency and accountability strategies. However, differences in institutional characteristics, levels of regulation, culture, and financial market development across countries lead to variations in the quality and impact of CSR disclosure on investor perceptions. This study uses a literature review method, examining scientific articles, international reports, and reputable academic publications that discuss the relationship between CSR disclosure and investor trust across developed and developing countries. The results indicate that comprehensive, credible, and consistent CSR disclosure tends to increase investor trust by reducing information asymmetry and risk perceptions, particularly in markets with strong levels of transparency and regulatory enforcement. However, the effectiveness of CSR disclosure is strongly influenced by each country's institutional context, including reporting standards, governance mechanisms, and investors' ESG literacy levels. This study provides a conceptual contribution by summarizing cross-country findings regarding the strategic role of CSR disclosure in building investor trust and its implications for companies, regulators, and global stakeholders.